2010
DOI: 10.1212/wnl.0b013e3181ed9c6b
|View full text |Cite
|
Sign up to set email alerts
|

Syndromes of nonfluent primary progressive aphasia

Abstract: Background: Despite recent work, the nosology of nonfluent primary progressive aphasia (PPA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 40 publications
5
103
1
5
Order By: Relevance
“…Several reports describe an increased frequency of AoS in patients with naPPA [40][41][42] . AoS is most prominent in conditions with co-occurring involuntary limb movements and poor limb motor control such as progressive supranuclear palsy syndrome (PSPS) and corticobasal syndrome (CBS), although AoS can occur without an accompanying extrapyramidal disorder, and AoS can occur as an isolated entity without other evidence of the language impairments found in naPPA 43,44 . An important problem has been difficulty quantifying AoS.…”
Section: Speech and Language Deficits In Nappamentioning
confidence: 99%
“…Several reports describe an increased frequency of AoS in patients with naPPA [40][41][42] . AoS is most prominent in conditions with co-occurring involuntary limb movements and poor limb motor control such as progressive supranuclear palsy syndrome (PSPS) and corticobasal syndrome (CBS), although AoS can occur without an accompanying extrapyramidal disorder, and AoS can occur as an isolated entity without other evidence of the language impairments found in naPPA 43,44 . An important problem has been difficulty quantifying AoS.…”
Section: Speech and Language Deficits In Nappamentioning
confidence: 99%
“…Many clinicians and researchers would still categorize AOS as a form of PNFA or as logopenic/phonologic aphasia [7]. Indeed, the features currently required for this diagnostic category appear on first glance very similar to AOS: Slowed, effortful, labored speech, sometimes with sound distortions [8].…”
Section: Discussionmentioning
confidence: 99%
“…In a voxel-based morphometric study correlating brain volume measures and disease severity scales, Rohrer et al found that the severity of AOS correlated with left posterior inferior frontal lobe atrophy, and that orofacial apraxia severity was more associated with left middle frontal, premotor and supplementary motor cortical atrophy [7]. AOS is associated with damage to the left postcentral gyrus in stroke patients.…”
Section: Brain Imaging and Apraxia Of Speechmentioning
confidence: 99%
“…In logopenic PPA cell loss is initially apparent in posterior-superior temporal lobe structures (Wilson et al, 2010). The behavioral profile is considered similar to that of vascular conduction aphasia (Gorno-Tempini, Dronkers, Rankin, Ogar, La Phengrasamy, Rosen, … Miller, 2004), although Rohrer, Rossor and Warren (2010) (Howard, Swinburn, & Porter, 2004)). With regard to sentence comprehension tested by sentence-picture matching tasks, understanding of written sentences was minimally impaired, but there was a marked impairment of spoken sentence comprehension (CAT Comprehension of spoken sentences 22/32; Comprehension of written sentences 30/32).…”
Section: Introductionmentioning
confidence: 99%